2012
DOI: 10.1371/journal.pone.0052397
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Loss of Tumor Suppressor miRNA-204 Promotes Cancer Cell Migration and Invasion by Activating AKT/mTOR/Rac1 Signaling and Actin Reorganization

Abstract: Increasing evidence suggests that chromosomal regions containing microRNAs are functionally important in cancers. Here, we show that genomic loci encoding miR-204 are frequently lost in multiple cancers, including ovarian cancers, pediatric renal tumors, and breast cancers. MiR-204 shows drastically reduced expression in several cancers and acts as a potent tumor suppressor, inhibiting tumor metastasis in vivo when systemically delivered. We demonstrated that miR-204 exerts its function by targeting genes invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 42 publications
(50 reference statements)
6
122
1
2
Order By: Relevance
“…In addition, CNV also results in aberrant expression of genes, including miRNAs (12). Imam and colleagues reported that the 9q21.12 chromosomal region containing miR-204 is frequently lost in ovarian cancers, breast cancers, and pediatric renal tumors (31). We observed no significant changes in the copy numbers of the miR-204 gene between the colorectal cancer and NCT samples, suggesting that CNV may not be a key mechanism leading to the downregulation of miR-204.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, CNV also results in aberrant expression of genes, including miRNAs (12). Imam and colleagues reported that the 9q21.12 chromosomal region containing miR-204 is frequently lost in ovarian cancers, breast cancers, and pediatric renal tumors (31). We observed no significant changes in the copy numbers of the miR-204 gene between the colorectal cancer and NCT samples, suggesting that CNV may not be a key mechanism leading to the downregulation of miR-204.…”
Section: Discussionmentioning
confidence: 50%
“…42 miR-204 also regulates expression of an oncogene, neurotrophic receptor tyrosine kinase B, and promotes metastasis in endometrial carcinoma. 43 Imam et al 44 showed that the genomic locus encoding miR-204 is frequently lost in multiple cancers, including breast and ovarian cancers, and pediatric renal tumors. They suggest that miR-204 targets distinct genes involved in tumorigenesis including BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the participation of miRNAs in breast cancer metastasis (Harquail et al, 2012). These studies have shown, for example, that miRlet-7, miR-584, and miR-204 inhibits cell motility by regulating the genes in the actin cytoskeleton pathway, implicating a central role for it in cytoskeletal dynamics (Imam et al, 2012;Fils-Aimé et al, 2013;Hu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%